Brief Report: Spatial Heterogeneity of Systemic Sclerosis in France: High Prevalence in the Northeast Region. Issue 7 (July 2016) - Meyer, Alain; Chifflot, Hélène; Chatelus, Emmanuel; Kleinmann, Jean‐François; Ronde‐Ousteau, Cécile; Klein, Delphine; Jégu, Jérémy; Geny, Bernard; Hirshi, Sandrine; Canuet, Matthieu; Blaison, Gilles; Kieffer, Pierre; et al.
Abstract : Objective: Alsace is a region in eastern France with a population of ∼2 million. All residents have high access to health care and an accredited referral center for SSc. Seeking care outside of this region is difficult because of the peculiar geography. The aim of this study was to assess the prevalence and spatial variation of systemic sclerosis (SSc) in eastern France. Methods: Data for SSc patients were obtained from 3 sources (all general practitioners and community specialists, capillaroscopy centers, and all public and private hospital records) and were used to estimate the prevalence of SSc. Surviving patients who resided in Alsace on January 1, 2008 and fulfilled the American College of Rheumatology and/or the LeRoy and Medsger criteria were included in this study. The clinical characteristics of the patients were also assessed. Potentially incomplete case ascertainment was corrected by capture–recapture analyses. Geographic disparities were assessed by spatial cluster analysis and by comparing our results with those for other geographic areas in the world for which data derived using similar methodology were available. Results: The review of 499 potential cases identified a total of 244 SSc patients. A trend toward a west‐to‐east gradient was observed but did not reach statistical significance. According to log‐linear modeling, an estimated 83.87 additional cases were missed. Thus, the SSc prevalence was 228.42 cases per million adult inhabitants of Alsace (95% confidence interval 203.70–253.14); this prevalence was significantly higher than that in 2 other regions of France and comparable with the reported prevalence in Detroit, Michigan. Conclusion: The stringent methodology used in the current study is very likely to provide an accurate estimation of the prevalence of SSc. Design similarity with 3 other surveys extends the scope of the results by identifying geographic disparities that were previously indistinguishable due to methodologic differences.